Extraction Optimization in Food Engineering - Tzia, Coustantina (Marcel Dekker, 2011)
The only comprehensive source on extraction process optimization, this book details the installation, construction, development, modeling, control, and economics of conventional and specialized extraction systems in the food processing industry. It supplies case studies for illustration of specific extraction systems in commercial food production. The book analyzes the properties and characteristics of liquid and aqueous extracting solvents and their impact on extraction operations, the supercritical fluid extraction technique, physicochemical and cost data for extraction process design, and the technical and safety aspects of plant design.